Effects of a DXA result letter on satisfaction, quality of life, and osteoporosis knowledge: a randomized controlled trial. Issue 1 (December 2016) - Edmonds, Stephanie; Cram, Peter; Lou, Yiyue; Jones, Michael; Roblin, Douglas; Saag, Kenneth; Wright, Nicole; Wolinsky, Fredric
Abstract Background Undiagnosed, or diagnosed and untreated osteoporosis (OP) increases the likelihood that falls result in hip fractures, decreased quality of life (QOL), and significant medical expenditures among older adults. We tested whether a tailored dual energy x-ray absorptiometry (DXA) test result letter and an accompanying educational bone-health brochure affected patient satisfaction, QOL, or OP knowledge. Methods The Patient Activation after DXA Result Notification (PAADRN) study was a double-blinded, pragmatic, randomized trial which enrolled patients from 2012 to 2014. We randomized 7, 749 patients presenting for DXA at three health care institutions in the United States who were ≥ 50 years old and able to understand English. Intervention patients received a tailored letter four weeks after DXA containing their results, 10-year fracture risk, and a bone-health educational brochure. Control patients received the results of their DXA per the usual practices of their providers and institutions. Satisfaction with bone health care, QOL, and OP knowledge were assessed at baseline and 12- and 52-weeks after DXA. Intention-to-treat analyses used multiple imputation for missing data and random effects regression models to adjust for clustering within providers and covariates. Results At 12-weeks 6, 728 (86.8 %) and at 52-weeks 6, 103 participants (78.8 %) completed their follow-up interviews. The intervention group was more satisfied with their bone health care compared to the usual care group at both their 12- and 52-week follow-ups (standardized effect size = 0.28 at 12-weeks and 0.17 at 52-weeks, p  < 0.001). There were no differences between the intervention and usual care groups in QOL or OP knowledge at either time point. Conclusions A tailored DXA result letter and bone-health educational brochure sent to patients improved patient satisfaction with bone-related health care. Trial registration Clinical Trials.gov Identifier:NCT01507662 First received: December 8, 2011.